Subclasses Of Multivalent Harmonic Mappings Defined By Convolution. - Ali, R. M.; Stephen, B. Adolf; Subramanian, K. G. (2009)

(untitled)
Harmonic mappings have been recently investigated from the perspective of geometric function theory. These mappings are important in the study of minimal surfaces. Although harmonic mappings need not be analytic, they have been studied as generalizations of conformal mappings. The seminal works of Clunie and Sheil-Small [4] and Sheil-Small [B] showed that while certain classical results for conformal mappings have analogues for harmonic mappings, many other basic questions remain unsolved.